Influence of Krypton Seeding on DD Fusion Neutron Production: Evaluation Methodology for Plasma Focus Optimization - Talebitaher, A.; Lee, S.; Kalaiselvi, S. M. P.; Verma, R.; Lee, P.; Springham, S. V.; Tan, T. L.; Rawat, R. S. (Springer US, 2015)
A sub-kilo-Joule plasma focus device (FMPF- 3, 14 kV/235 J) was operated with deuterium–krypton admixtures (of 1, 2 and 5 % Kr by volume) to study the influence of admixture ratio on neutron yield (Yn). Experiments were performed for different insulator sleeve lengths and cathode geometries. The results reveal that for a carefully optimized electrode geometry the highest average neutron yield is obtained with pure deuterium as the operating gas, whereas krypton seeding leads to a reduction in Yn. We argue that the electrode geometry and electrical coupling play critical roles in determining the influence of gas admixtures; and that for an optimized plasma focus device D2-Kr admixtures may give little or no neutron yield enhancement relative to pure D2 operation and so the admixture operation is an evaluation methodology to determine the level of optimization of device geometry.